Studi Kasus Prosedur Pemeriksaan Ct Scan Urografi Klinis Batu Ginjal di Instalasi Radiologi RSUD Brebes - Yuti Meriani; Fisnandya Meita Astari; Amril Mukmin (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Urinary tract examination with the CT-Scan modality is considered superior to other imaging modalities because it produces better image resolution, clear anatomical details, and is able to accurately detect abnormalities. At the Radiology Installation of Brebes Hospital, the CT-Scan Urography examination is carried out without fasting requirements. Patients are only asked to remove metal objects from the abdominal area and hold urination before the examination begins. This aims to keep the urinary bladder (VU) fully filled so that it facilitates the evaluation of the anatomy of the urinary system, especially in detecting kidney stones which are the main complaints of patients. This study aims to find out in detail the procedure for CT-Scan Urography clinical urography of kidney stones, as well as the reasons why patients are asked to hold urination and are not asked to fast before the procedure is performed. The research method used is a mix method, which is a combination of qualitative and quantitative, with data collection through observation, interviews, and documentation. The research sample consisted of 3 patients who underwent CT-Scan Urography clinical examination of kidney stones at the Radiology Installation of Brebes Hospital. The results of the study showed that the procedure started from the patient's preparation, such as removing metal objects, drinking mineral water, and holding urination so that the VU was fully filled, thus helping the visualization of organs and urinary tract. This examination does not require fasting because the CT-Scan modality is able to provide a clear picture of the anatomy of the urinary tract without interference from the digestive system. These findings confirm that the CT-Scan Urography procedure at Brebes Hospital is simple, effective, practical, and provides optimal diagnostic results for patients.